2014
DOI: 10.1002/tox.22094
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of liver kinase B1 in hydroquinone‐induced toxicity of murine fetal liver and bone marrow hematopoietic stem cells

Abstract: Epidemiological studies suggest that the increasing incidence of childhood leukemia may be due to maternal exposure to benzene, which is a known human carcinogen; however, the mechanisms involved remain unknown. Liver Kinase B1 (LKB1) acts as a regulator of cellular energy metabolism and functions to regulate hematopoietic stem cell (HSC) homeostasis. We hypothesize that LKB1 contributes to the deregulation of fetal or bone hematopoiesis caused by the benzene metabolite hydroquinone (HQ). To evaluate this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…LKB1 plays an important role in the generation and activity of mature T cells . In hematopoietic stem cells, LKB1 serves as an essential agent to preserve the viability, modulate quiescence and metabolic homeostasis, and monitor energy metabolism and cell cycles . Furthermore, several studies using tissue‐specific LKB1 knockout murine models have showed that LKB1 is crucial to the pool of primordial follicles .…”
mentioning
confidence: 99%
“…LKB1 plays an important role in the generation and activity of mature T cells . In hematopoietic stem cells, LKB1 serves as an essential agent to preserve the viability, modulate quiescence and metabolic homeostasis, and monitor energy metabolism and cell cycles . Furthermore, several studies using tissue‐specific LKB1 knockout murine models have showed that LKB1 is crucial to the pool of primordial follicles .…”
mentioning
confidence: 99%
“…Previous studies have revealed that different doses of HQ may induce apoptosis ( 24 , 25 ). Treatment with a low dose of HQ for 24 h induced HQ-mediated apoptosis in murine fetal livers and bone marrow hematopoietic cells ( 24 ). Treatment with a high dose of HQ for 24 h promoted apoptosis in bone marrow-derived mesenchymal stem cells ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Benzene, one of the earliest industrial chemicals, has been demonstrated to affect the health of a large number of workers 1,2 and can lead to tumor formation, such as acute myeloid leukemia and aplastic anemia, through occupational exposure. Hydroquinone (HQ), also known as one of the main metabolites of benzene in vivo, plays an important role in the toxicity effect of benzene 3–7 . HQ has been shown to cause DNA damage, such as double‐strand breaks (DSBs), 8 chromosomal aberration, 9 sister chromatid exchange, 10 and genomic instability, 11 in cultured human and animal cells and expression changes in ncRNAs, such as long noncoding RNAs (lncRNAs) 12 and small noncoding RNAs (miRNAs) 13 .…”
Section: Introductionmentioning
confidence: 99%